2023
DOI: 10.1038/s44220-023-00116-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to intrinsic rewards is domain general and related to mental health

Bastien Blain,
India Pinhorn,
Tali Sharot

Abstract: Humans frequently engage in intrinsically rewarding activities (for example, consuming art, reading). Despite such activities seeming diverse, we show that sensitivity to intrinsic rewards is domain general and associated with mental health. In this cross-sectional study, participants online (N = 483) were presented with putative visual, cognitive and social intrinsic rewards as well as monetary rewards and neutral stimuli. All rewards elicited positive feelings (were ‘liked’), generated consummatory behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
(65 reference statements)
2
1
0
Order By: Relevance
“…This fits well with the clinical features of anhedonia (or depression), i.e. an inability to enjoy, a lack of motivation to participate in typically rewarding activities [40], [86], [87], and difficulty using reward-related information to guide decisions [42], [88], [89]. Turning to apathy, we observed our most surprising, yet robust, transdiagnostic finding.…”
Section: Discussionsupporting
confidence: 80%
“…This fits well with the clinical features of anhedonia (or depression), i.e. an inability to enjoy, a lack of motivation to participate in typically rewarding activities [40], [86], [87], and difficulty using reward-related information to guide decisions [42], [88], [89]. Turning to apathy, we observed our most surprising, yet robust, transdiagnostic finding.…”
Section: Discussionsupporting
confidence: 80%
“…A complementary genetic perspective on music reward sensitivity could be a particularly fruitful strategy to better understand human musicality and affect because we found genetic influences to be primarily separate from other relevant perceptual-affective processes, such as music perceptual abilities and general reward sensitivity. The dissociation between the genetics of music reward sensitivity and general perceptual and reward processing mirrors the finding that specific musical anhedonia, i.e., blunted or absent hedonic responses from music stimuli, exists in the absence of any perceptual or generalised reward deficit 12,16 , yet contrasts other findings suggesting sensitivity to intrinsic rewards to be domain general 50 . This implies that genetic variance associated with music reward sensitivity, beyond perceptual and general reward processing, can be used to better disentangle and understand the mechanisms involved in sensory-specific experiences of enjoyment.…”
Section: Discussionsupporting
confidence: 53%
“…It should be noted that recent evidence has suggested that intrinsic motivation may lead to an analogous set of findings to those predicted by adaptive coding models (Molinaro and Collins, 2023). The capacity for intrinsic motivation also might vary across individuals (Blain et al, 2023), leading to an alternative set of predictions generated by intrinsic motivation models, which could be pursued in future work. Another scenario I did not consider was whether alpha influences the magnitude of the neural RPE signal directly (as opposed to indirectly by affecting prior expectations).…”
Section: Limitationsmentioning
confidence: 95%